Encounters with Europe in an Era of Domestic and International Turmoil: Is Turkey a De-Europeanising Candidate Country?. Issue 1 (2nd January 2016) - Aydın-Düzgit, Senem; Kaliber, Alper
Abstract: This article provides a novel conceptual framework to understand the impact of the European Union on Turkish politics and policies in the aftermath of the opening of accession negotiations in 2005. It argues that the post-2005 developments in Turkey not only attest to lesser and more limited Europeanisation, but also entail a process that is increasingly gaining momentum in the country and which is referred to as 'de-Europeanisation'.